Preparation process of high-strength high-temperature-resistant flame-retardant magnesium-aluminum alloy

CN118699374BActive Publication Date: 2026-10-09JIANGSU ZHONGFU ALUMINUM MAGNESIUM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410743093.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2026-10-09
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

变形用镁合金材料的强度σb在160-320MPa之间,传统的6系铝合金的强度σb在200-450MPa之间,但是应用于新能源汽车中的结构件材料中6系铝合金的强度σb要求在350-450MPa之间,可商业化应用于新能源汽车中的结构件材料中的价格经济的变形用镁合金材料强度σb还无法满足新能源汽车行业的使用需求

Benefits of technology

[0035] 1. This application has good impact resistance, ductility, toughness, hot working performance, mechanical strength, and good high temperature flame retardancy, which meets the requirements of new energy vehicles for magnesium-aluminum alloy materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004885485580000161
    Figure BDA0004885485580000161
  • Figure BDA0004885485580000171
    Figure BDA0004885485580000171
Patent Text Reader

Abstract

The application relates to the technical field of magnesium-aluminum alloy preparation, in particular to a preparation process of high-strength high-temperature-resistant flame-retardant magnesium-aluminum alloy. The high-strength high-temperature-resistant flame-retardant magnesium-aluminum alloy comprises an inner core layer and an outer protective layer, the inner core layer is made of 2-4 wt% of surface metal-doped modified carbon nanotubes, 0.5-2 wt% of surface metal-doped modified nanometer molybdenum disulfide nanosheets, 0.05-0.20 wt% of Ce powder, 0.05-0.40 wt% of Y powder and the rest of magnesium-aluminum alloy powder; and the outer protective layer is made of 0.5-2 wt% of surface metal-doped modified carbon nanotubes, 3-6 wt% of surface metal-doped modified nanometer molybdenum disulfide nanosheets, 0.5-2 wt% of surface metal-doped modified graphene, 0.05-0.20 wt% of Ce powder, 0.05-0.40 wt% of Y powder and the rest of magnesium-aluminum alloy powder. The application has good strength and ductile toughness and good high-temperature-resistant flame retardance, and meets the demand of new energy vehicles for magnesium-aluminum alloy materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of magnesium-aluminum alloy preparation technology, and in particular to a preparation process for a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy. Background Technology

[0002] Magnesium-aluminum alloys are alloys made with magnesium as the matrix, aluminum as the main auxiliary reinforcing phase, and trace alloying elements such as Ag, Zn, V, Ti, Mn, Ni, Sb, and Si. They have advantages such as low density, high specific strength, high specific elastic modulus, good heat dissipation, good vibration damping, and high impact load capacity. They are widely used in the automotive, aerospace, transportation, chemical and other industrial fields.

[0003] With the rapid development of the new energy vehicle industry, the requirements for lightweight structural materials are becoming increasingly stringent. Magnesium-aluminum alloys, with their lower density than traditional 6-series aluminum alloys and superior impact load resistance, have become an ideal structural material for new energy vehicles. Existing wrought magnesium alloys are typically extruded, rolled, and molded at 300–500℃ to obtain ideal structural components. The strength σ of wrought magnesium alloy materials… b Between 160-320 MPa, the strength σ of traditional 6-series aluminum alloys b The strength σ of 6-series aluminum alloys used in structural components of new energy vehicles is between 200-450 MPa. b The required strength (σ) of deformable magnesium alloy materials is between 350-450 MPa, making them commercially viable and cost-effective for structural components in new energy vehicles. b This still cannot meet the needs of the new energy vehicle industry. Therefore, the applicant provides a preparation process for a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy. Summary of the Invention

[0004] To address the aforementioned technical problems, this application provides a preparation process for a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0005] The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy provided in this application is achieved through the following scheme:

[0006] A high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy has a sandwich structure, comprising an inner core layer that improves ductility and toughness, and an outer protective layer that provides flame retardancy and high-temperature resistance. The inner core layer is prepared by powder metallurgy from the following raw materials in the indicated mass percentages: 2-4 wt% surface-doped metal-modified carbon nanotubes, 0.5-2 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.05-0.20 wt% Ce powder, 0.05-0.40 wt% Y powder, and the balance being magnesium-aluminum alloy powder. The outer protective layer is composed of… The following raw materials, in the indicated mass percentages, are prepared by powder metallurgy: 0.5-2 wt% surface-doped metal-modified carbon nanotubes, 3-6 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.5-2 wt% surface-doped metal-modified graphene, 0.05-0.20 wt% Ce powder, 0.05-0.40 wt% Y powder, with the balance being magnesium-aluminum alloy powder; the magnesium-aluminum alloy powder is an MB-based magnesium-aluminum alloy; the preparation process of the high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy includes the following steps:

[0007] Step 1: Preparation of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene;

[0008] Step 2, Preparation of Mixed Alloy Powder A: Accurately metered surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, Ce powder, Y powder, and magnesium-aluminum alloy powder are dispersed and mixed at high speed at 600-800 rpm for 15-30 min to obtain mixed alloy powder A.

[0009] Simultaneously prepare mixed alloy powder B: accurately measure and disperse and mix surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, surface-doped metal-modified graphene, Ce powder, Y powder, and magnesium-aluminum alloy powder at 600-800 rpm for 15-30 min to obtain mixed alloy powder B.

[0010] Step 3: First, lay a layer of mixed alloy powder A in the forming mold, then lay another layer of mixed alloy powder A on top of the mixed alloy powder A, and then perform cold isostatic pressing. Apply pressure at 5-10 MPa / s to 240-280 MPa, hold the pressure for 300-400s, reduce the pressure at 1-3 MPa / s to 120-150 MPa, hold the pressure for 300-400s, and then reduce the pressure at 5-10 MPa / s to 0 MPa to obtain the pre-pressed part.

[0011] Step 4: Transfer the forming mold with the pre-pressed part to a muffle furnace, heat it at 50-100℃ / min to 680-740℃ and hold for 30-60 min, then cool it at 5-20℃ / min to 520-540℃ and hold for 4-8 h. After cooling to room temperature, heat it again at 5-20℃ / min to 240-260℃ and hold for 2-6 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0012] The high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy in this application has a sandwich structure. The outer layer of magnesium-aluminum alloy provides excellent high-temperature resistance and flame retardancy while also possessing superior strength. The core layer of magnesium-aluminum alloy has good ductility, toughness, and strength. The high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy produced by combining these two layers exhibits good ductility, toughness, hot working properties, mechanical strength, and excellent high-temperature resistance and flame retardancy, meeting the requirements of new energy vehicles for magnesium-aluminum alloy materials. Furthermore, the preparation method of this application is a relatively simple and mature powder metallurgy process, with low difficulty in industrial implementation, facilitating mass production.

[0013] Preferably, in step three, a layer of mixed alloy powder A is first laid in the molding die, then another layer of mixed alloy powder A is laid on top of the mixed alloy powder A, and then cold isostatic pressing is performed, with pressure increased from 10 MPa / s to 280 MPa, held for 300 s, pressure decreased from 3 MPa / s to 150 MPa, held for 300 s, and then decreased to 0 MPa from 10 MPa / s to obtain a pre-pressed part.

[0014] By adopting the above technical solution, a pre-pressed part with high density and uniform dispersion of reinforcing phase can be obtained, thereby ensuring that the prepared magnesium-aluminum alloy material has the advantages of good impact resistance, ductility and toughness, hot working performance, mechanical strength and high temperature flame retardancy.

[0015] Preferably, in step three, a layer of mixed alloy powder A is first laid in the molding die, then another layer of mixed alloy powder A is laid on top of the mixed alloy powder A, and then cold isostatic pressing is performed, with pressure increased from 5 MPa / s to 240 MPa, held for 300 s, pressure decreased from 1 MPa / s to 120 MPa, held for 400 s, and pressure decreased from 5 MPa / s to 0 MPa to obtain a pre-pressed part.

[0016] By adopting the above technical solutions, the density of the pre-pressed parts can be further improved, which in turn helps to improve the overall impact resistance, ductility, hot working performance, mechanical strength, and high-temperature flame retardancy.

[0017] Preferably, in step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated at 80-100℃ / min to 680-740℃ and held for 30-60 min, then cooled at 5-10℃ / min to 520℃ and held for 6-8 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating at 15-20℃ / min to 250℃ and holding for 3-4 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0018] By adopting the above technical solutions, high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy materials with superior ductility and toughness can be obtained.

[0019] Preferably, in step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated to 680-740℃ at 80-100℃ / min and held for 30-60 min, then cooled to 560℃ at 15-20℃ / min and held for 4-6 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating to 280℃ at 5-10℃ / min and holding for 1-2 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0020] By adopting the above technical solutions, high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy materials with superior mechanical strength and heat resistance can be obtained.

[0021] Preferably, the inner core layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 3.2-3.6 wt% surface-doped metal-modified carbon nanotubes, 0.8-1.6 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.08-0.12 wt% Ce powder, 0.24-0.32 wt% Y powder, and the balance being magnesium-aluminum alloy powder MB1.

[0022] By adopting the above technical solutions, the physicochemical properties of the inner core magnesium-aluminum alloy can be improved while controlling the overall production cost.

[0023] Preferably, the outer protective layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 1.2-1.8 wt% surface-doped metal-modified carbon nanotubes, 4.8-6.0 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.6-1.2 wt% surface-doped metal-modified graphene, 0.08-0.12 wt% Ce powder, 0.24-0.32 wt% Y powder, and the balance being magnesium-aluminum alloy powder MB2.

[0024] By adopting the above technical solution, the physicochemical properties of the outer magnesium-aluminum alloy can be improved while controlling the overall production cost. Introducing Ce and Y powders into the magnesium-aluminum alloy increases the bonding force of Mg atoms, reduces the atomic diffusion rate, and improves the overall high-temperature resistance.

[0025] Preferably, the surface-doped metal-modified carbon nanotubes include multi-walled carbon nanotubes and nanoscale doped metals loaded on the surface of the multi-walled carbon nanotubes. The nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

[0026] Preferably, the surface-doped metal-modified molybdenum disulfide nanosheets include molybdenum disulfide nanosheets and nanoscale doped metals loaded on the surface of the molybdenum disulfide nanosheets. The nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

[0027] Preferably, the surface-doped metal-modified graphene includes monolayer graphene and nanoscale doped metal loaded on the surface of monolayer graphene. The nanoscale doped metal is one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metal is one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

[0028] Nanotechnology was used to improve the compatibility of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene with the magnesium matrix, enabling them to be more uniformly dispersed within the magnesium-aluminum alloy. Furthermore, the nanoscale doping of the metals on the surface can form a reinforcing alloy with the magnesium-aluminum alloy matrix, further improving the physicochemical properties of the prepared magnesium-aluminum alloy material.

[0029] Specifically, the use of nanoscale doped metals, such as magnesium in the form of nanoclusters or quantum dots, primarily improves the interfacial compatibility between surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene and the matrix magnesium. This allows them to be uniformly dispersed within the magnesium-aluminum alloy, enabling magnesium-magnesium fusion bonding and aluminum-magnesium alloying. 17 Al 12 Mutual reinforcement.

[0030] Specifically, the nanoscale doped metal is aluminum in the form of nanoclusters or quantum dots, and Mg is formed at the interface between aluminum and the magnesium matrix on the surface of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene. 17 Al 12 Mutual reinforcement.

[0031] Specifically, the nanoscale doped metal is silver in the form of nanoclusters or quantum dots. The silver on the surface of metal-modified carbon nanotubes, metal-modified molybdenum disulfide nanosheets, and metal-modified graphene can dissolve into the magnesium matrix. The interstitial solid solution atoms cause non-spherical symmetry distortion, which has the effect of solid solution enhancement.

[0032] Specifically, the nanoscale doped metal is zirconium in the form of nanoclusters or quantum dots. The zirconium on the surface of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene reacts with the magnesium matrix to refine the grains and improve corrosion resistance and heat resistance.

[0033] Specifically, the nanoscale doped metal is bismuth in the form of nanoclusters or quantum dots. Surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene surfaces with bismuth dissolved in the matrix magnesium to form Mg3Sb2 can refine the matrix grains and generate grain boundary strengthening. Moreover, its dispersion strengthening can improve high-temperature performance.

[0034] In summary, this application has the following advantages:

[0035] 1. This application has good impact resistance, ductility, toughness, hot working performance, mechanical strength, and good high temperature flame retardancy, which meets the requirements of new energy vehicles for magnesium-aluminum alloy materials.

[0036] 2. The preparation method of this application is a powder metallurgy process that is relatively simple and mature, with low difficulty in industrial implementation and easy to achieve mass production. Detailed Implementation

[0037] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.

[0038] Example

[0039] A high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy has a sandwich structure, comprising an inner core layer and an outer sheath. The outer magnesium-aluminum alloy material provides excellent high-temperature resistance and flame retardancy while also possessing superior strength. The core magnesium-aluminum alloy material exhibits good ductility, toughness, and strength. Therefore, the resulting high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy material possesses good impact resistance, ductility, toughness, hot working properties, mechanical strength, and excellent high-temperature flame retardancy, meeting the requirements of new energy vehicles for magnesium-aluminum alloy materials.

[0040] The inner core layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 2-4 wt% surface-doped metal-modified carbon nanotubes, 0.5-2 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.05-0.20 wt% Ce powder, 0.05-0.40 wt% Y powder, and the balance being magnesium-aluminum alloy powder. The magnesium-aluminum alloy powder is an MB-based magnesium-aluminum alloy powder.

[0041] Preferably, the inner core layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 3.2-3.6 wt% of surface-doped metal-modified carbon nanotubes, 0.8-1.6 wt% of surface-doped metal-modified molybdenum disulfide nanosheets, 0.08-0.12 wt% of Ce powder, 0.24-0.32 wt% of Y powder, and the balance being magnesium-aluminum alloy powder MB1.

[0042] The outer sheath is prepared by powder metallurgy from the following raw materials in the following mass percentages: 0.5-2 wt% surface-doped metal-modified carbon nanotubes, 3-6 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.5-2 wt% surface-doped metal-modified graphene, 0.05-0.20 wt% Ce powder, 0.05-0.40 wt% Y powder, and the balance being magnesium-aluminum alloy powder. The magnesium-aluminum alloy powder is MB-based magnesium-aluminum alloy powder.

[0043] Preferably, the outer protective layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 1.2-1.8 wt% of surface-doped metal-modified carbon nanotubes, 4.8-6.0 wt% of surface-doped metal-modified molybdenum disulfide nanosheets, 0.6-1.2 wt% of surface-doped metal-modified graphene, 0.08-0.12 wt% of Ce powder, 0.24-0.32 wt% of Y powder, and the balance being magnesium-aluminum alloy powder MB2.

[0044] The surface-doped metal-modified carbon nanotubes in the inner core and outer sheath include multi-walled carbon nanotubes and nanoscale doped metals loaded on the surface of multi-walled carbon nanotubes. The nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

[0045] The surface-doped metal-modified molybdenum disulfide nanosheets in the inner core and outer sheath include molybdenum disulfide nanosheets and nanoscale doped metals loaded on the surface of the molybdenum disulfide nanosheets. The nanoscale doped metals are one or more combinations of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more combinations of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

[0046] The surface-doped metal-modified graphene in the inner core and outer sheath includes monolayer graphene and nanoscale doped metals loaded on the surface of monolayer graphene. The nanoscale doped metals are one or more combinations of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more combinations of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

[0047] Specifically, the use of nanoscale doped metals, such as magnesium in the form of nanoclusters or quantum dots, primarily improves the interfacial compatibility between surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene and the matrix magnesium. This allows them to be uniformly dispersed within the magnesium-aluminum alloy, enabling magnesium-magnesium fusion bonding and aluminum-magnesium alloying. 17 Al 12 Mutual reinforcement.

[0048] Specifically, the nanoscale doped metal is aluminum in the form of nanoclusters or quantum dots, and Mg is formed at the interface between aluminum and the magnesium matrix on the surface of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene. 17 Al 12 Mutual reinforcement.

[0049] Specifically, the nanoscale doped metal is silver in the form of nanoclusters or quantum dots. The silver on the surface of metal-modified carbon nanotubes, metal-modified molybdenum disulfide nanosheets, and metal-modified graphene can dissolve into the magnesium matrix. The interstitial solid solution atoms cause non-spherical symmetry distortion, which has the effect of solid solution enhancement.

[0050] Specifically, the nanoscale doped metal is zirconium in the form of nanoclusters or quantum dots. The zirconium on the surface of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene reacts with the magnesium matrix to refine the grains and improve corrosion resistance and heat resistance.

[0051] Specifically, the nanoscale doped metal is bismuth in the form of nanoclusters or quantum dots. Surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene surfaces with bismuth dissolved in the matrix magnesium to form Mg3Sb2 can refine the matrix grains and generate grain boundary strengthening. Moreover, its dispersion strengthening can improve high-temperature performance.

[0052] A preparation method for a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy includes the following steps:

[0053] Step 1: Preparation of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene;

[0054] Surface-doped metal-modified molybdenum disulfide nanosheets can be prepared by high-speed ball milling, chemical vapor deposition, or sol-gel method.

[0055] Metal-modified carbon nanotubes were prepared by chemical vapor deposition or sol-gel method.

[0056] Metal-modified graphene with surface doping was prepared by chemical vapor deposition or sol-gel method;

[0057] Step 2, Preparation of Mixed Alloy Powder A: Accurately metered surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, Ce powder, Y powder, and magnesium-aluminum alloy powder are dispersed and mixed at high speed at 600-800 rpm for 15-30 min to obtain mixed alloy powder A.

[0058] Simultaneously prepare mixed alloy powder B: accurately measure and disperse and mix surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, surface-doped metal-modified graphene, Ce powder, Y powder, and magnesium-aluminum alloy powder at 600-800 rpm for 15-30 min to obtain mixed alloy powder B.

[0059] Step 3: First, lay a layer of mixed alloy powder A in the forming mold, then lay another layer of mixed alloy powder A on top of the mixed alloy powder A, and then perform cold isostatic pressing. Apply pressure at 5-10 MPa / s to 240-280 MPa, hold the pressure for 300-400s, reduce the pressure at 1-3 MPa / s to 120-150 MPa, hold the pressure for 300-400s, and then reduce the pressure at 5-10 MPa / s to 0 MPa to obtain the pre-pressed part.

[0060] Preferably, in step three, a layer of mixed alloy powder A is first laid in the forming mold, then another layer of mixed alloy powder A is laid on top of the mixed alloy powder A, and then cold isostatic pressing is performed, with pressure increased from 10 MPa / s to 280 MPa, held for 300 s, pressure decreased from 3 MPa / s to 150 MPa, held for 300 s, and pressure decreased from 10 MPa / s to 0 MPa to obtain a pre-pressed part;

[0061] Preferably, in step three, a layer of mixed alloy powder A is first laid in the forming mold, then another layer of mixed alloy powder A is laid on top of the mixed alloy powder A, and then cold isostatic pressing is performed, with pressure increased from 5 MPa / s to 240 MPa, held for 300 s, pressure decreased from 1 MPa / s to 120 MPa, held for 400 s, and pressure decreased from 5 MPa / s to 0 MPa to obtain a pre-pressed part;

[0062] Step 4: Transfer the forming mold with the pre-pressed part to a muffle furnace, heat it at 50-100℃ / min to 680-740℃ and hold it for 30-60 min, then cool it at 5-20℃ / min to 520-540℃ and hold it for 4-8 h. After cooling to room temperature, heat it again at 5-20℃ / min to 240-260℃ and hold it for 2-6 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0063] Preferably, in step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated to 680-740℃ at 80-100℃ / min and held for 30-60 min, then cooled to 520℃ at 5-10℃ / min and held for 6-8 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating to 250℃ at 15-20℃ / min and holding for 3-4 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0064] Preferably, in step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated to 680-740℃ at 80-100℃ / min and held for 30-60 min, then cooled to 560℃ at 15-20℃ / min and held for 4-6 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating to 280℃ at 5-10℃ / min and holding for 1-2 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0065] Example 1: A high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy sandwich structure, comprising an inner core layer and an outer sheath layer.

[0066] The inner core layer is made of 3.5 wt% surface-doped metal-modified carbon nanotubes, 1.5 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.08 wt% Ce powder, 0.32 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB1 (atomized spherical aluminum-magnesium alloy powder MB1 customized by Hubei Langbowan Biomedical Co., Ltd., with an average particle size of 15-25 micrometers).

[0067] The outer protective layer is made of 1.6 wt% surface-doped metal-modified carbon nanotubes, 5.4 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.8 wt% surface-doped metal-modified graphene, 0.08 wt% Ce powder, 0.32 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB2 (custom-made atomized spherical aluminum-magnesium alloy powder MB2 by Hubei Langbowan Biomedical Co., Ltd., with an average particle size of 15-25 micrometers).

[0068] A preparation process for a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy includes the following steps:

[0069] Step 1: Preparation method of surface-doped magnesium-modified carbon nanotubes: First, prepare a 36.4 g / L magnesium nitrate hexahydrate ethanol solution under nitrogen protection; simultaneously, prepare a 2.8 g / L NaBH4 aqueous solution under nitrogen protection. Add 2 g of multi-walled carbon nanotubes (outer diameter 8-15 nm, inner diameter 2-4 nm, brand Zhongke Leiming) to 200 mL of NaBH4 aqueous solution, and disperse the multi-walled carbon nanotubes in an aqueous solution at an ultrasonic frequency of 40 kHz / 800 W for 60 min. Under nitrogen protection, 200 mL of magnesium nitrate ethanol solution was added dropwise to an aqueous dispersion of multi-walled carbon nanotubes at a rate of 1 mL / min. After the addition was complete, the reaction continued for 1 h. The process of settling, pouring out the supernatant, and washing with deionized water was repeated three times. The resulting precipitate was then vacuum-dried for 24 h at a temperature of 80 °C and a vacuum of 0.1 Pa. The resulting solid was then placed in a planetary ball mill and ball-milled at 120 rpm for 60 min to obtain surface-doped magnesium-modified carbon nanotubes.

[0070] Preparation method of surface-doped magnesium-modified molybdenum disulfide nanosheets (sol-gel method): 3.6 g of magnesium nitrate hexahydrate was dissolved in 0.3 L of deionized water, and then 5 g of molybdenum disulfide nanosheets (nano-molybdenum disulfide, particle size 100 nm, brand Maoguo Nano) were added. The mixture was dispersed under ultrasonic frequency of 40 kHz / 800 W for 30 min, and then a 3.5 wt% sodium hydroxide aqueous solution was added until Mg was completely precipitated to form Mg(OH)₂. The mixture was then mechanically stirred at 160 rpm / 1 h and allowed to stand for 12 h to obtain Mg(OH)₂ / nano-molybdenum disulfide nanosheets. Rice-based binary colloids were washed three times with deionized water and then vacuum filtered to obtain solid powder. The powder was then vacuum-dried for 12 hours at a set temperature of 80°C and a set vacuum degree of 0.1 Pa. Under an air atmosphere, the powder was first calcined at 400°C for 2 hours at a rate of 10°C / min. Then, under a reducing atmosphere of hydrogen-argon mixture (volume ratio of 1:4), the powder was reduced at 640°C for 6 hours. After the furnace was opened and the powder was allowed to cool naturally to room temperature, the resulting solid was placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium-modified molybdenum disulfide nanosheets.

[0071] Preparation method of surface-doped magnesium-modified graphene: First, prepare a 36.4 g / L magnesium nitrate hexahydrate ethanol solution under nitrogen protection; simultaneously, prepare a 2.8 g / L NaBH4 aqueous solution under nitrogen protection. Add 2 g of graphene (nanographene sheets, <30 layers, diameter 5-10 μm, thickness 4-20 nm, brand Zhongke Leiming) to 200 mL of NaBH4 aqueous solution, and disperse under ultrasonic frequency 40 kHz / 800 W for 60 min to obtain graphene water. Aluminum dispersion; under nitrogen protection, 200 mL of magnesium nitrate ethanol solution was added dropwise to the graphene aqueous dispersion at a rate of 1 mL / min. After the addition was complete, the reaction continued for 1 h. The process of settling, pouring out the supernatant, and washing with deionized water was repeated three times. The resulting precipitate was then vacuum-dried for 24 h at a temperature of 80 °C and a vacuum of 0.1 Pa. The resulting solid was then placed in a planetary ball mill and ball-milled at 120 rpm for 120 min to obtain graphene modified with magnesium doping.

[0072] Step 2, Preparation of Mixed Alloy Powder A: The accurately measured surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, Ce powder, Y powder, and magnesium-aluminum alloy powder are dispersed and mixed at 800 rpm for 30 min to obtain mixed alloy powder A.

[0073] Simultaneously prepare mixed alloy powder B: accurately measure and disperse the surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, surface-doped metal-modified graphene, Ce powder, Y powder, and magnesium-aluminum alloy powder at 800 rpm for 30 min to obtain mixed alloy powder B.

[0074] Step 3: First, lay a layer of mixed alloy powder A in the forming mold, then lay another layer of mixed alloy powder A on top of the first layer. Then, perform cold isostatic pressing, applying pressure at 10 MPa / s to 280 MPa, holding the pressure for 300 s, then reducing the pressure at 3 MPa / s to 150 MPa, holding the pressure for 300 s, and then reducing the pressure at 10 MPa / s to 0 MPa to obtain the pre-pressed part.

[0075] Step 4: Transfer the forming mold with the pre-pressed part to a muffle furnace, heat it to 740℃ at 100℃ / min and hold for 60 min, then cool it to 520℃ at 5℃ / min and hold for 8 h. After cooling to room temperature, heat it again by heating it to 250℃ at 20℃ / min and holding for 3 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0076] The difference between Example 2 and Example 1 is as follows: In step three, a layer of mixed alloy powder A is first laid in the molding die, and then another layer of mixed alloy powder A is laid on top of the mixed alloy powder A. Then, cold isostatic pressing is performed, with the pressure increased from 5 MPa / s to 240 MPa, held for 300 s, then reduced to 120 MPa at 1 MPa / s, held for 400 s, and then reduced to 0 MPa at 5 MPa / s to obtain the pre-pressed part.

[0077] The difference between Example 3 and Example 1 is as follows: In step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated to 680°C at 100°C / min and held for 60 min, then cooled to 560°C at 20°C / min and held for 4 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating to 250°C at 5°C / min and holding for 4 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0078] The difference between Example 4 and Example 2 is as follows: In step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated to 680°C at 100°C / min and held for 60 min, then cooled to 560°C at 20°C / min and held for 6 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating to 280°C at 5°C / min and holding for 2 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0079] The difference between Example 5 and Example 1 is that the inner core layer is made of 2 wt% surface-doped metal-modified carbon nanotubes, 0.5 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.1 wt% Ce powder, 0.2 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB1.

[0080] The difference between Example 6 and Example 1 is that the inner core layer is made of 4 wt% surface-doped metal-modified carbon nanotubes, 2 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.15 wt% Ce powder, 0.35 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB1.

[0081] The difference between Example 7 and Example 1 is that the outer protective layer is made of 0.5 wt% surface-doped metal-modified carbon nanotubes, 3 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.5 wt% surface-doped metal-modified graphene, 0.12 wt% Ce powder, 0.28 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB2.

[0082] The difference between Example 8 and Example 1 is that the outer protective layer is made of 2 wt% surface-doped metal-modified carbon nanotubes, 6.0 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 2 wt% surface-doped metal-modified graphene, 0.08 wt% Ce powder, 0.32 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB2.

[0083] The difference between Example 9 and Example 1 is as follows: Step 1, the preparation method of surface-doped magnesium + aluminum modified carbon nanotubes: First, under nitrogen protection, prepare a 37.9 g / L concentration of magnesium nitrate hexahydrate (16.8 g / L) + aluminum nitrate nonahydrate (21.9 g / L) ethanol solution, which is mixture a; simultaneously, under nitrogen protection, prepare a 3.05 g / L concentration of NaBH4 aqueous solution, add 2 g of multi-walled carbon nanotubes to 200 mL of NaBH4 aqueous solution, and disperse under ultrasonic frequency of 40 kHz / 800 W. A 60-minute aqueous dispersion of multi-walled carbon nanotubes was prepared. Under nitrogen protection, mixture a was added dropwise to the aqueous dispersion of multi-walled carbon nanotubes at a rate of 1 ml / min. After the addition was complete, the reaction continued for 1 hour. The process of settling, pouring out the supernatant, and washing with deionized water was repeated three times. The resulting precipitate was then vacuum-dried for 24 hours at a temperature of 80°C and a vacuum of 0.1 Pa. The resulting solid was then placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium and aluminum modified carbon nanotubes.

[0084] Preparation method of surface-doped magnesium and aluminum modified molybdenum disulfide nanosheets: 1.76 g magnesium nitrate hexahydrate and 1.98 g aluminum nitrate nonahydrate were dissolved in 0.3 L of deionized water, and then 5 g of molybdenum disulfide nanosheets were added. The mixture was dispersed ultrasonically at 40 kHz / 800 W for 30 min, followed by the addition of a 3.5 wt% sodium hydroxide aqueous solution until Mg and Al were completely precipitated to form Mg(OH)2 and Al(OH)3. The mixture was then mechanically stirred at 160 rpm / 1 h and allowed to stand for 12 h to obtain a binary colloid of Mg(OH)2 + Al(OH)3 / molybdenum disulfide nanosheets. After washing the binary colloid three times with water, the solid powder was obtained by vacuum filtration. The powder was then vacuum-dried for 12 hours at a set temperature of 80℃ and a set vacuum degree of 0.1 Pa. Under an air atmosphere, the powder was first calcined at 240℃ for 1 hour at a rate of 10℃ / min, and then calcined at 400℃ for 2 hours at a rate of 10℃ / min. The powder was then reduced at 640℃ for 6 hours under a reducing atmosphere of hydrogen-argon mixture (volume ratio of 1:4). After the furnace was opened and the powder was naturally cooled to room temperature, the resulting solid was placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium + aluminum modified molybdenum disulfide nanosheets.

[0085] Preparation method of surface-doped magnesium and aluminum modified graphene: Preparation method of surface-doped magnesium and aluminum modified carbon nanotubes: First, prepare a 37.9 g / L magnesium nitrate hexahydrate (16.8 g / L) + aluminum nitrate nonahydrate (21.9 g / L) ethanol solution under nitrogen protection, which is mixture a; simultaneously, prepare a 3.05 g / L NaBH4 aqueous solution under nitrogen protection, add 2 g of graphene to 200 mL of NaBH4 aqueous solution, and sonicate at 40 kHz / 800 W. Aqueous graphene dispersion was obtained by dispersing for 60 min. Mixture a was added dropwise to the aqueous graphene dispersion at a rate of 1 ml / min under nitrogen protection. After the addition was complete, the reaction continued for 1 h. The process of settling, pouring out the supernatant, and washing with deionized water was repeated three times. The precipitate was then vacuum-dried for 24 h at a temperature of 80 °C and a vacuum of 0.1 Pa. The resulting solid was then placed in a planetary ball mill and ball-milled at 120 rpm for 60 min to obtain graphene modified with magnesium and aluminum doping.

[0086] The difference between Example 10 and Example 1 is as follows: Step 1, the preparation method of surface-doped magnesium + silver modified carbon nanotubes: First, a 35.4 g / L magnesium nitrate hexahydrate (31.2 g / L) + silver nitrate (4.2 g / L) ethanol solution is prepared under nitrogen protection, which is mixture a; simultaneously, a 3.2 g / L NaBH4 aqueous solution is prepared under nitrogen protection, and 2 g of multi-walled carbon nanotubes are added to 200 mL of NaBH4 aqueous solution and dispersed under ultrasonic frequency of 40 kHz / 800 W for 60 minutes. A multi-walled carbon nanotube aqueous dispersion was prepared by adding mixture a at a rate of 1 ml / min to the multi-walled carbon nanotube aqueous dispersion under nitrogen protection. After the addition was complete, the reaction continued for 1 hour. The process of settling, pouring out the supernatant, and washing with deionized water was repeated three times. The precipitate was then vacuum-dried for 24 hours at a temperature of 80°C and a vacuum of 0.1 Pa. The resulting solid was then placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium + silver modified carbon nanotubes.

[0087] Preparation method of surface-doped magnesium + silver modified molybdenum disulfide nanosheets: 2.24 g magnesium nitrate hexahydrate and 0.96 g silver nitrate were dissolved in 0.3 L of deionized water, and then 5 g of molybdenum disulfide nanosheets were added. The mixture was dispersed under ultrasonic frequency of 40 kHz / 800 W for 30 min, followed by the addition of a 2 wt% sodium hydroxide aqueous solution until Mg and Ag were completely precipitated to form Mg(OH)2 and AgOH. The mixture was then mechanically stirred at 160 rpm / 1 h and allowed to stand for 12 h to obtain a binary colloid of Mg(OH)2 + AgOH / molybdenum disulfide nanosheets. The binary colloid was then subjected to deionized water. After washing the colloid three times, the solid powder was obtained by vacuum filtration. The powder was then vacuum-dried for 12 hours at a set temperature of 80°C and a set vacuum degree of 0.1 Pa. Under an air atmosphere, the powder was first calcined at 200°C for 1 hour at a rate of 10°C / min, and then calcined at 400°C for 2 hours at a rate of 10°C / min. The powder was then reduced at 640°C for 6 hours under a reducing atmosphere of hydrogen-argon mixture (volume ratio of 1:4). After the furnace was opened and the powder was allowed to cool naturally to room temperature, the resulting solid was placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium + silver modified molybdenum disulfide nanosheets.

[0088] The difference between the preparation method of surface-doped magnesium and silver modified graphene and the preparation method of surface-doped magnesium and silver modified carbon nanotubes lies in the fact that multi-walled carbon nanotubes are replaced with graphene of equal mass.

[0089] The difference between Example 11 and Example 1 is as follows: Step 1, the preparation method of surface-doped magnesium + bismuth modified carbon nanotubes: First, a 36.1 g / L magnesium nitrate hexahydrate (27.4 g / L) + bismuth nitrate pentahydrate (8.7 g / L) ethanol solution is prepared under nitrogen protection, which is mixture a; simultaneously, a 3.35 g / L NaBH4 aqueous solution is prepared under nitrogen protection, and 2 g of multi-walled carbon nanotubes are added to 200 mL of NaBH4 aqueous solution and dispersed under ultrasonic frequency of 40 kHz / 800 W. A 60-minute aqueous dispersion of multi-walled carbon nanotubes was prepared. Under nitrogen protection, mixture a was added dropwise to the aqueous dispersion of multi-walled carbon nanotubes at a rate of 1 ml / min. After the addition was complete, the reaction continued for 1 hour. The process of settling, pouring out the supernatant, and washing with deionized water was repeated three times. The resulting precipitate was then vacuum-dried for 24 hours at a temperature of 80°C and a vacuum of 0.1 Pa. The resulting solid was then placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium + bismuth modified carbon nanotubes.

[0090] Preparation method of surface-doped magnesium + bismuth modified molybdenum disulfide nanosheets: 2.54 g of magnesium nitrate hexahydrate and 1.36 g of bismuth nitrate pentahydrate were dissolved in 0.3 L of deionized water, and then 5 g of molybdenum disulfide nanosheets were added. The mixture was dispersed under ultrasonic frequency of 40 kHz / 800 W for 30 min, and then a 3 wt% sodium hydroxide aqueous solution was added until Mg and Bi were completely precipitated to form Mg(OH)2 and Bi(OH)3. The mixture was then mechanically stirred at 160 rpm / 1 h and allowed to stand for 12 h to obtain Mg(OH)2 + Bi(OH)3 / molybdenum disulfide nanosheets. Rice-based binary colloids were washed three times with deionized water and then vacuum filtered to obtain solid powder. The powder was then vacuum-dried for 12 hours at a set temperature of 80°C and a set vacuum degree of 0.1 Pa. Under an air atmosphere, the powder was first calcined at 450°C for 2 hours at a rate of 10°C / min. Then, under a reducing atmosphere of hydrogen-argon mixture (volume ratio of 1:4), the powder was reduced at 580°C for 6 hours. After the furnace was opened and the powder was allowed to cool naturally to room temperature, the resulting solid was placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium + bismuth modified molybdenum disulfide nanosheets.

[0091] The difference between the preparation method of surface-doped magnesium + bismuth modified graphene and the preparation method of surface-doped magnesium + bismuth modified carbon nanotubes lies in the fact that multi-walled carbon nanotubes are replaced with graphene of equal mass.

[0092] The difference between Example 12 and Example 1 is as follows: Step 1, the preparation method of surface-doped magnesium + aluminum + bismuth modified carbon nanotubes: First, under nitrogen protection, prepare a 37.3 g / L concentration of magnesium nitrate hexahydrate (20.8 g / L) + aluminum nitrate nonahydrate (10.7 g / L) + bismuth nitrate pentahydrate (5.8 g / L) ethanol solution, which is mixture a; simultaneously, under nitrogen protection, prepare a 3.35 g / L concentration of NaBH4 aqueous solution, add 2 g of multi-walled carbon nanotubes to 200 mL of NaBH4 aqueous solution, and sonicate at a frequency of 40 kHz. A multi-walled carbon nanotube aqueous dispersion was prepared by dispersing the mixture at 800W for 60 min. Under nitrogen protection, the mixture a was added dropwise to the multi-walled carbon nanotube aqueous dispersion at 1 ml / min. After the addition was complete, the reaction continued for 1 h. The process of settling, pouring out the supernatant, and washing with deionized water was repeated three times. The precipitate was then vacuum-dried for 24 h at a set temperature of 80℃ and a set vacuum degree of 0.1 Pa. The resulting solid was then placed in a planetary ball mill and ball-milled at 120 rpm for 60 min to obtain surface-doped magnesium + aluminum + bismuth modified carbon nanotubes.

[0093] Preparation method of surface-doped magnesium + aluminum + bismuth modified molybdenum disulfide nanosheets: 2.14 g magnesium nitrate hexahydrate, 1.69 g aluminum nitrate nonahydrate, and 4.08 g bismuth nitrate pentahydrate were dissolved in 0.35 L of deionized water. Then, 5 g of molybdenum disulfide nanosheets were added and dispersed under ultrasonic frequency of 40 kHz / 800 W for 30 min. A 2 wt% sodium hydroxide aqueous solution was then added until Mg, Al, and Bi were completely precipitated to form Mg(OH)₂, Al(OH)₃, and Bi(OH)₃. The mixture was then mechanically stirred at 160 rpm / 1 h and allowed to stand for 12 h to obtain Mg(OH)₂ + Bi(OH)₃ / nano-molybdenum disulfide. Nanosheet binary colloid; after washing the binary colloid three times with deionized water, the solid powder was obtained by vacuum filtration. The powder was then vacuum-dried for 12 hours at a set temperature of 80℃ and a set vacuum degree of 0.1 Pa. In an air atmosphere, the powder was first heated to 240℃ at 10℃ / min and held for 1 hour, then calcined at 450℃ at 10℃ / min for 2 hours. The powder was then reduced at 640℃ for 6 hours in a reducing atmosphere of hydrogen-argon mixture (volume ratio of 1:4). After the furnace was opened and the powder was naturally cooled to room temperature, the resulting solid was placed in a planetary ball mill and ball-milled at 120 rpm for 60 minutes to obtain surface-doped magnesium + aluminum + bismuth modified molybdenum disulfide nanosheets.

[0094] The difference between the preparation method of graphene modified by surface doping with magnesium, aluminum and bismuth and the preparation method of carbon nanotubes modified by surface doping with magnesium, aluminum and bismuth lies in the fact that multi-walled carbon nanotubes are replaced with graphene of equal mass.

[0095] The difference between Comparative Example 1 and Example 1 is that the inner core layer is made of 0.08 wt% Ce powder, 0.32 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB1. The outer sheath is made of 0.08 wt% Ce powder, 0.32 wt% Y powder, and the balance is magnesium-aluminum alloy powder MB2.

[0096] The difference between Comparative Example 2 and Example 1 is that the inner core layer is made of 3.5 wt% carbon nanotubes, 1.5 wt% molybdenum disulfide nanosheets, 0.08 wt% Ce powder, 0.32 wt% Y powder, and the balance being magnesium-aluminum alloy powder MB1. The outer sheath is made of 1.6 wt% carbon nanotubes, 5.4 wt% molybdenum disulfide nanosheets, 0.8 wt% graphene, 0.08 wt% Ce powder, 0.32 wt% Y powder, and the balance being magnesium-aluminum alloy powder MB2.

[0097] The difference between Comparative Example 3 and Example 1 is that in step three, a layer of mixed alloy powder A is first laid in the molding die, then another layer of mixed alloy powder A is laid on top of the mixed alloy powder A, and then cold isostatic pressing is performed. The pressure is increased from 20 MPa / s to 250 MPa, held for 10 minutes, and then reduced to 0 MPa at 20 MPa / s to obtain the pre-pressed part.

[0098] The difference between Comparative Example 4 and Example 1 is that in step four, the molding die with the pre-pressed part is transferred to a muffle furnace, heated to 680°C at 50°C / min and held for 60 min, then cooled to room temperature and subjected to heat treatment, heated to 320°C at 20°C / min and held for 4 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

[0099] Table 1: Test parameters of magnesium-aluminum alloy materials in Examples 1-10 and Comparative Examples 1-4

[0100]

[0101]

[0102] Note: The control group was MB2 magnesium-aluminum alloy / T4 material. 1. Tensile properties were determined according to GB / T 16865-2013 "Tension Test Specimens and Methods for Processed Products of Wrought Aluminum, Magnesium and Their Alloys". 2. High-Temperature Flame Retardant Performance Test Method: Magnesium-aluminum alloy cubes of 10*10*10mm were prepared according to the preparation methods of Examples 1-12 and Comparative Examples 1-4 above. The edges were ground off before testing. The specific experimental method is as follows: The sample was heated to 1000℃ in a crucible melting furnace. The furnace temperature was observed after the sample burned. The test was repeated three times, and the average ignition point of the aluminum-magnesium alloy was recorded. 3. High-Temperature Oxidation Performance Test: Magnesium-aluminum alloy cuboids measuring 10*10*2mm were prepared according to the preparation methods described in Examples 1-12 and Comparative Examples 1-4. A constant-temperature resistance furnace was used to test the high-temperature oxidation resistance of the samples. The oxidation medium was still air, the experimental temperature was 575℃, and the cumulative oxidation time was 8 hours. Before the oxidation experiment, the mass M1 and surface area S of each sample were measured. After the oxidation experiment, the weight M2 of the sample was measured using an electronic balance with an accuracy of 0.1 mg. The rate of change of mass per unit area (mg / cm²) was calculated. 3 ) = (M2-M1) / S.

[0103] As can be seen from Examples 1-12 and Comparative Examples 1-4 and Table 1, the high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy prepared in this application has good strength and ductility toughness, as well as good high-temperature flame retardancy, which meets the requirements of new energy vehicles for magnesium-aluminum alloy materials.

[0104] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A preparation process for a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy, characterized in that: The high-strength, high-temperature resistant, and flame-retardant magnesium-aluminum alloy has a sandwich structure, comprising an inner core layer that improves ductility and toughness, and an outer protective layer that provides flame retardancy and high-temperature resistance. The inner core layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 2-4 wt% surface-doped metal-modified carbon nanotubes, 0.5-2 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.05-0.20 wt% Ce powder, 0.05-0.40 wt% Y powder, and the balance being magnesium-aluminum alloy powder. The outer protective layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 0.5-2 wt% surface-doped metal-modified carbon nanotubes, 3-6 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.5-2 wt% surface-doped metal-modified graphene, 0.05-0.20 wt% Ce powder, 0.05-0.40 wt% Y powder, and the balance being magnesium-aluminum alloy powder. The magnesium-aluminum alloy powder is an MB-series magnesium-aluminum alloy; The preparation process of the high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy includes the following steps: Step 1: Preparation of surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, and surface-doped metal-modified graphene; Step 2, Preparation of Mixed Alloy Powder A: Accurately metered surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, Ce powder, Y powder, and magnesium-aluminum alloy powder are dispersed and mixed at high speed at 600-800 rpm for 15-30 min to obtain mixed alloy powder A. Simultaneously prepare mixed alloy powder B: accurately measure and disperse the surface-doped metal-modified carbon nanotubes, surface-doped metal-modified molybdenum disulfide nanosheets, surface-doped metal-modified graphene, Ce powder, Y powder, and magnesium-aluminum alloy powder at 600-800 rpm for 15-30 min to obtain mixed alloy powder B. Step 3: First, lay a layer of mixed alloy powder A in the forming mold, then lay a layer of mixed alloy powder B on top of mixed alloy powder A, and then perform cold isostatic pressing. Apply pressure at 5-10 MPa / s to 240-280 MPa, hold the pressure for 300-400s, reduce the pressure at 1-3 MPa / s to 120-150 MPa, hold the pressure for 300-400s, and then reduce the pressure at 5-10 MPa / s to 0 MPa to obtain the pre-pressed part. Step four: Transfer the forming mold with the pre-pressed part to a muffle furnace, heat it at 50-100℃ / min to 680-740℃ and hold for 30-60 min, then cool it at 5-20℃ / min to 520-540℃ and hold for 4-8 h. After cooling to room temperature, perform heat treatment by heating at 5-20℃ / min to 240-260℃ and holding for 2-6 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

2. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 1, characterized in that: In step three, a layer of mixed alloy powder A is first laid in the molding die, then a layer of mixed alloy powder B is laid on top of mixed alloy powder A, and then cold isostatic pressing is performed. The pressure is increased from 10 MPa / s to 280 MPa, held for 300 s, then decreased to 150 MPa at 3 MPa / s, held for 300 s, and then decreased to 0 MPa at 10 MPa / s to obtain a pre-pressed part.

3. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 1, characterized in that: In step three, a layer of mixed alloy powder A is first laid in the molding die, then a layer of mixed alloy powder B is laid on top of mixed alloy powder A, and then cold isostatic pressing is performed. The pressure is increased from 5 MPa / s to 240 MPa, held for 300 s, then decreased to 120 MPa at 1 MPa / s, held for 400 s, and then decreased to 0 MPa at 5 MPa / s to obtain a pre-pressed part.

4. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 2 or 3, characterized in that: In step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated to 680-740℃ at 80-100℃ / min and held for 30-60 min, then cooled to 520℃ at 5-10℃ / min and held for 6-8 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating to 250℃ at 15-20℃ / min and holding for 3-4 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

5. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 2 or 3, characterized in that: In step four, the forming mold with the pre-pressed part is transferred to a muffle furnace, heated to 680-740℃ at 80-100℃ / min and held for 30-60 min, then cooled to 560℃ at 15-20℃ / min and held for 4-6 h. After cooling to room temperature, the furnace is opened and then heat-treated by heating to 280℃ at 5-10℃ / min and holding for 1-2 h to obtain a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy.

6. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 1, characterized in that: The inner core layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 3.2-3.6 wt% surface-doped metal-modified carbon nanotubes, 0.8-1.6 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.08-0.12 wt% Ce powder, 0.24-0.32 wt% Y powder, and the balance being magnesium-aluminum alloy powder MB1.

7. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 1, characterized in that: The outer protective layer is prepared by powder metallurgy from the following raw materials in the following mass percentages: 1.2-1.8 wt% surface-doped metal-modified carbon nanotubes, 4.8-6.0 wt% surface-doped metal-modified molybdenum disulfide nanosheets, 0.6-1.2 wt% surface-doped metal-modified graphene, 0.08-0.12 wt% Ce powder, 0.24-0.32 wt% Y powder, and the balance being magnesium-aluminum alloy powder MB2.

8. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 6 or 7, characterized in that: The surface-doped metal-modified carbon nanotubes include multi-walled carbon nanotubes and nanoscale doped metals loaded on the surface of the multi-walled carbon nanotubes. The nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

9. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 6 or 7, characterized in that: The surface-doped metal-modified molybdenum disulfide nanosheets include molybdenum disulfide nanosheets and nanoscale doped metals loaded on the surface of the molybdenum disulfide nanosheets. The nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

10. The preparation process of a high-strength, high-temperature resistant, flame-retardant magnesium-aluminum alloy according to claim 6 or 7, characterized in that: The surface-doped metal-modified graphene includes monolayer graphene and nanoscale doped metals loaded on the surface of monolayer graphene. The nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of nanoclusters; or the nanoscale doped metals are one or more of silver, magnesium, aluminum, bismuth, and zirconium in the form of quantum dots.

Citation Information

Patent Citations

  • Flame-proof magnesium alloy added with beryllium and strontium and preparation method thereof

    CN101104901A

  • Impact-resisting and scratching-resisting mobile phone metal back shell

    CN107971483A